Ecological Assessment of Autonomy in Instrumental Activities of Daily Living in Dementia Patients by the Means of an Automatic Video Monitoring System - König, Alexandra; Crispim-Junior, Carlos Fernando; Covella, Alvaro Gomez Uria; Bremond, Francois; Derreumaux, Alexandre; Bensadoun, Gregory; David, Renaud; Verhey, Frans; Aalten, Pauline; Robert, Philippe (Frontiers in Aging Neuroscience, 2015)
Currently, the assessment of autonomy and functional ability involves clinical rating scales. However, scales are often limited in their ability to provide objective and sensitive information. In contrast, information and communication technologies may overcome these limitations by capturing more fully the functional, as well as cognitive disturbances associated with Alzheimer disease (AD). We investigated the quantitative assessment of the autonomy of dementia patients based not only on gait analysis but also on the participant performance on Instrumental Activities of Daily Living (IADL) automatically recognized by a video event monitoring system (EMS). Three groups of participants (healthy controls, Mild Cognitive Impairment and AD patients) had to carry out a standardized scenario consisting of physical tasks (single and dual task) and several IADLs such as preparing a pillbox or making a phone call while being recorded. After, video sensor data was processed by an event monitoring system that automatically extracts kinematic parameters of the participants’ gait and recognizes their carried out activities. These parameters were then used for the assessment of the participants’ performance levels, here referred as autonomy. Autonomy assessment were approached as classification task using artificial intelligence methods that takes as input the parameters extracted by the event monitoring system, here referred as behavioral data. Activities were accurately recognized by the EMS with high precision. The most accurately recognized activities were: ‘prepare medication’ with 93% and ‘using phone’ with 89% precision. The diagnostic group classifier obtained a precision of 73.46% when combining the analyses of physical tasks with IADLs. In a further analysis, the created autonomy group classifier which obtained a precision of 83.67% when combining physical tasks and IADLs. Results suggest that it is possible to quantitatively assess IADL functioning supported by an EMS.